Enhanced thermal performances of PCM heat sinks enabled by layer-by-layer-assembled carbon nanotube–polyethylenimine functional interfaces. (15th August 2022) - Kim, Jiheon; Lee, Jaemin; Song, Chanho; Yun, Jaeyoung; Choi, Wonjoon
Graphical abstract: Highlights: Carbon nanotube-polyethylenimine coatings on PCM heat sinks are developed. Layer-by-Layer (LbL) solution processing enables nanocoatings of charged precursors. LbL processes lead to optimal porous thermal interfaces between PCM and heat sinks. PCM-LbL heat sinks enhance cooling performances for transient thermal loads. LbL coatings improve active sites-contact interfaces for liquid–solid phase change. Abstract: Rationally designed hybrids of heat sinks (HSs) and phase change materials (PCMs) can mutually complement their fundamental limitations. However, integrating PCMs into HSs inevitably incurs additional thermal resistances and degradation during solid–liquid phase transitions owing to unstable contact interfaces. Herein, we report layer-by-layer (LbL)-assembled multiwalled carbon nanotube (MWCNT)–polyethyleneimine (PEI) functional interfaces between the PCM and HS surfaces to enhance thermal management capabilities. The LbL process used in this study involves direct fabrication of electrostatically adhered nanocoatings of multiple materials via a solution process, which resulted in facile formation of MWCNT-PEI percolation networks on an aluminum HS. The PCM-HS was completed by filling the HS channels with a PCM (n-eicosane). The functional interface increased the active surface areas for thermal transport and optimized the porous structures for the stabilization of the PCM–HS boundary under repetitive solid–liquid phase changes. Comparison of the fabricated specimens (bare and PCM-filled HSs without LbL interfaces) elucidated the enhanced thermal performances in transient-static operating conditions. This was confirmed by experimentally measuring the real-time temperature responses at various levels of heating power and the time delays to reach the set point temperatures, indicating a more than 10% improvement in effectiveness using the LbL interface. Furthermore, the LbL interfaces efficiently alleviated thermal shock or overload under intermittent thermal loads. The developed LbL interface offers a tunable–scalable method to fabricate PCM-filled HSs with advanced thermal properties that cannot be achieved using a conventional HS.